Patterns of Complementary and Alternative Medicine Use among Turkish Cancer Patients - TOPTAŞ, TAYFUR (MARY ANN LIEBERT INC, 2013)
Background: The aim of this study was to determine the tendency to use complementary/alternative medicine (CAM) by patients with cancer in Turkey, and to compare sociodemographic and medical characteristics, perceptions, and quality of life of users and nonusers of CAM. Methods: A total of 1060 cancer patients were asked to complete a questionnaire about the use of CAM along with the European Organization for Research and Treatment of Cancer Life Quality Questionnaire C30 (EORTC QLQ-C30). Medical information was obtained from hospital chart records. Results: The response rate was 40.1% (425/1060). Use of at least one kind of CAM was identified in 57.4% of the patients. Herbal medications (95%), spiritual/religious affiliations (23.3%), multivitamins/antioxidants (18.4%), and transcendental meditation/yoga (8.6%) were the leading CAM methods. In multivariate analysis, CAM use was found to be associated with age (> 60 years) only. Average expenditure on CAMs was 30 U.S. dollars (USD) per patient per month. The most common causes of CAM use were belief in their efficacy (41.3%) and intimate interaction with CAM users (37.2%). Only 41% of the users had informed their doctors that they used CAM. QLQ scores were similar between CAM users and nonusers. Of all participants, 15.5% had psychiatric support. Proportions of regular antidepressant and analgesic use were 16.4%, and 46.3%, respectively. CAM users had worse appetite scores. There was no difference in terms of other scales between the groups. Conclusions: This study showed that CAM use is widespread among Turkish cancer patients and CAM use does not improve QLQ scores. Physicians should be aware of high CAM utilization rate in patients with cancer and should better understand the factors directing the patients to such treatments.
Keywords: QUALITY-OF-LIFE; BREAST-CANCER; THERAPIES; TURKEY; PREVALENCE; DETERMINANTS; ATTITUDES; REMEDIES